Penerapan Pembelajaran Pokok Bahasan Perbandingan Trigonometri dengan Menggunakan Media Peta Konsep pada Siswa - Ika Sartika (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This study aims to study the effectiveness of learning the subject of trigonometric comparison using media concept maps in class X Asy-Syafiiyah International Medan High School TP 2019/2020, to see how much changes in student learning outcomes taught with media concept maps in class X high school students Asy-Syafiiyah International Medan TP 2019/2020. The population in this study were all students of class X at Ash-Syafiiyah International Medan. The results of this study indicate that (1) the level of mastery of students there are 7 students or 18% the level of mastery is very high, 8 students or 21% the level of mastery is high, 18 students or 46% level of mastery is moderate, 5 students or 13% mastery level is low, 1 student or 2% mastery level is very low. This means that class X Asy-Syafiiyah International Medan students have mastered trigonometric comparisons with the application of concept map media. (2) Completeness of learning there are 33 students or 85% who have completed individually and 6 students or 15% who have not finished individually. This means that students have finished classically (3) Out of ten (10) TPKs are expected, achieved by students there are 10 or 100% TPK completed, (4) Observation results indicate that the implementation of learning is in the range of values 3 to 4 (5) The magnitude of the change in learning outcomes of students taught with media concept maps in class X Ash-Syafiiyah International Medan is 2.00, it can be concluded that the application of concept maps is effectively used in learning trigonometric comparisons.